Stereotypy and variation of the mating call in the Lusitanian toadfish, Halobatrachus didactylus - Amorim, Maria Clara Pessoa (2012)
Signal attributes should show different degrees of variability depending on the information to be conveyed. Species identity is usually associated with stereotyped features of a signal, whereas other types of information such as individual quality and motivation are associated with signal plasticity. Lusitanian toadfish males form aggregations during the breeding season and emit a tonal advertisement call (the boatwhistle) to attract mates to their nests. We test the hypothesis that the boatwhistle can convey information both on individual identity and motivation by checking how signal parameters vary with time. We study how the physical (tide level) and social (calling alone or in a chorus) environments and male calling rate affect this advertisement signal and how all these external and internal factors (environment, social and male motivation) blend to modulate the Lusitanian toadfish’s advertisement call. Boatwhistles of each male were very stereotyped in short periods of time (minutes), but intra-male signal variability greatly increased in a longer time scale (days). Nevertheless, significant differences among males could still be found even in a long time scale. Pulse period was the acoustic feature that most contributed to discriminate among males. Tide level and male calling rate modulated boatwhistle characteristics, and there was a differential effect of tide on call attributes depending on male calling rate. Social acoustic environment only affected calling rate. These results suggest that inter-individual differences in call characteristics and call plasticity may mediate both male– male assessment and mate choice.